Waiting for Josiah: The Judges. By Philippe Guillaume. Pp. xiv + 325 . (Journal for the Study of the Old Testament Supplement Series, 385.) London: T. & T. Clark (a Continuum imprint), 2004. isbn 0 8264 6988 4. £75 - Tollington, Janet E. (The journal of theological studies, 2005)
This monograph is basically Guillaume's doctoral thesis: as such it is carefully structured with frequent recapitulation of the developing argument, plus extensive footnotes and bibliography. Nonetheless it is a very good read, despite scattered evidence that English is not the author's first language and the poor standards of editorial proofreading. Guillaume's primary intention was to read the Book of Judges as an independent text, rather than as integral to Noth's so-called Deuteronomistic History, with the expectation that if he achieved this aim, it would undermine the whole theory associated with Noth's work.